In silico analysis of Schmidtea mediterranea TIR domain-containing proteins. (September 2018) - Tsoumtsa, Landry Laure; Sougoufora, Seynabou; Torre, Cedric; Lemichez, Emmanuel; Pontarotti, Pierre; Ghigo, Eric
Abstract: While genetic evidence points towards an absence of Toll-Like Receptors (TLRs) in Platyhelminthes, the Toll/IL-1 Receptor (TIR)-domains that drive the assembly of signalling complexes downstream TLR are present in these organisms. Here, we undertook the characterisation of the repertoire of TIR-domain containing proteins in Schmidtea mediterranea in order to gain valuable information on TLR evolution in metazoan. We report the presence of twenty proteins containing between one and two TIR domains. In addition, our phylogenetic-based reconstruction approach identified Smed-SARM and Smed-MyD88 as conserved TLR adaptors. Highlights: Landscape of TIR-domain containing proteins described in planarians. First description of MyD88 homologue in platyhelminthes. A membrane bound TIR-domain containing protein emerges as TLR Like protein. Analysis revealed planarian-specific expansion of TIR-domain containing proteins.